Alterations in redox homeostasis following repeated sprint training program (Kinesiology, 2020)
This study examined the effects of a 6-week repeated sprint training program on redox-based homeostasis and its association with muscle damage. Fifteen male physical education students (aged 20.0 ± 1.0 years; body weight 77.7 ± 6.0 kg; height 181.0 ± 4.4 cm; % body fat 8.7 ± 3.0 %) familiar with intermittent activities volunteered to participate in the study. Experimental training program consisted of 2-3 sets of 6-10 straight-line or shuttle 20-meter repeated sprints with departures every 25 seconds and 2-minute inter-set passive recovery. The training intervention lasted for six weeks during which 18 training sessions were performed. The levels of 15-F2t-isoprostanes were measured in plasma and 24-hour urine; superoxide dismutase, glutathione peroxidase and glutathione reductase in erythrocytes; uric acid and creatine kinase in serum after; the first, and the penultimate training session. The level of muscle damage following repeated sprint exercise was not significantly altered (402 to 496 U/L; p=.151) and had no significant associations with changes in marker depicting redox-homeostasis. A significant increase in plasma 15-F2t-isoprostanes (0.32 to 0.56 ng/mL; p=.026), and subsequent decrease in glutathione reductase (1070.4 to 502.9 U/g Hb; p